Spinal Cord Injury: A Systematic Review and Network Meta-Analysis of Therapeutic Strategies Based on 15 Types of Stem Cells in Animal Models - Shang, Zhizhong; Wang, Ruirui; Li, Dongliang; Chen, Jinlei; Zhang, Baolin; Wang, Mingchuan; Wang, Xin; Wanyan, Pingping (Frontiers in Pharmacology, 2022)
Abstract Objective The optimal therapeutic strategies of stem cells for spinal cord injury (SCI) are fully explored in animal studies to promote the translation of preclinical findings to clinical practice, also provide a guidance for future animal and clinical studies. Methods PubMed, Web of science, Embase, CNKI, Wangfang, VIP, CBM were searched from inception to September 2021. Screening of search results, data extraction, and literature quality evaluation were undertaken independently by two reviewers. Results and Discussion A total of 188 studies were included for data analysis. Results of traditional meta-analysis showed that all 15 stem cells could significantly improve locomotor function of animals with SCI, and results of a further network meta-analysis showed that adipose-derived mesenchymal stem cells had the greatest therapeutic potential for SCI. Moreover, 1×106 of stem cells were the optimal dose, transplantation in the subacute phase (3-14 days, excluding 3 days) was the optimal timing and intralesional transplantation was the optimal route. However, the evidence of current animal studies is of limited quality, and more high-quality original studies are needed to further explore the optimal therapeutic strategies of stem cells, while the design and implementation of experiments, also measurement and reporting of outcomes for animal studies need to be further enhanced and standardized to reduce the risk when the results of animal studies are translated to the clinic.